2020
DOI: 10.1002/sctm.20-0127
|View full text |Cite
|
Sign up to set email alerts
|

The human bone marrow harbors a CD45− CD11B+ cell progenitor permitting rapid microglia-like cell derivative approaches

Abstract: Microglia, the immune sentinel of the central nervous system (CNS), are generated from yolk sac erythromyeloid progenitors that populate the developing CNS. Interestingly, a specific type of bone marrow-derived monocyte is able to express a yolk sac microglial signature and populate CNS in disease. Here we have examined human bone marrow (hBM) in an attempt to identify novel cell sources for generating microglia-like cells to use in cell-based therapies and in vitro modeling. We demonstrate that hBM stroma har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(148 reference statements)
0
6
0
Order By: Relevance
“…As CD11b is also expressed by peripherally-derived myeloid cells in the CNS ( Fischer and Reichmann, 2001 ; Greter et al, 2015 ), it must be paired together with other markers to identify microglia more specifically. It is often co-utilized with universally expressed leukocyte surface proteins such as CD45, the combination of which has utility for identifying microglia by flow cytometry ( Bruzelius et al, 2021 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…As CD11b is also expressed by peripherally-derived myeloid cells in the CNS ( Fischer and Reichmann, 2001 ; Greter et al, 2015 ), it must be paired together with other markers to identify microglia more specifically. It is often co-utilized with universally expressed leukocyte surface proteins such as CD45, the combination of which has utility for identifying microglia by flow cytometry ( Bruzelius et al, 2021 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
“…CD45, present on all leukocytes in varying levels, and CD68, a lysosomal marker present in endosomes and lysosomes of the mononuclear phagocytic lineages [including microglia, border-associated macrophages (BAMs) and macrophages], can be used to identify microglia in the CNS and other immune cells ( Hendrickx et al, 2017 ; Rangaraju et al, 2018 ; Waller et al, 2019 ; Bruzelius et al, 2021 ). CD45, a protein tyrosine phosphatase, plays a role in the proliferation and differentiation of immune cells ( Penninger et al, 2001 ), but tends to be expressed at lower levels on microglia than on CNS-infiltrating myeloid cells during non-inflammatory conditions, while CD68 is associated with inflammatory responses, phagolysosomal activity, and the regulation of antigen presentation ( Song et al, 2011 ; Chistiakov et al, 2017 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
“…Recently, it has been reported that the stromal fraction of human BM contains a CD45 − CD11b + precursor, apparently devoted to producing cells labeled with Iba-1 and expressing genes of developing (as RUNX1, SPF1, and CSF1R) and adult human microglia (including P2RY12, TMEM119, and ITGAM). Moreover, cells produced from these precursors show increased phagocytic capacity, are activated in response to LPS, and integrate into human brain tissue, conserving the expression of TMEM119 marker (Bruzelius et al, 2021). Therefore, it seems that human BM cells might be able to give rise to new microglia.…”
Section: Human Vs Mouse Microgliamentioning
confidence: 99%
“…As a recent study had reported that murine bone marrow-derived microglia possessing a yolk sac microglial signature could populate the diseased central nervous stem, 13 researchers led by Tania Ramos-Moreno (Lund University, Sweden) recently sought to examine the human bone marrow in the hope of identifying cells that may foster the rapid and reliable generation of human microglia for therapeutic purposes. In their recent STEM CELLS Translational Medicine article, 5 Bruzelius et al report on the detection, isolation, and characterization of intermediatelyspecified myeloid microglial progenitors present within the human bone marrow stroma that express human-specific consensus adult microglial genes. Encouragingly, the authors also described protocols for the efficient in vitro expansion of these microglial progenitors (which employs a stromal cell feeder layer) and the generation of microglia that retain the expression of important marker genes.…”
Section: Featured Articles Human Bone Marrow-derived Microglial Progenitors As a Starting Point For Microglial Therapies And Modelingmentioning
confidence: 99%
“…our Featured Articles published this month in STEM CELLS Translational Medicine, Bruzelius et al describe the discovery of microglialike precursors in the human bone marrow that may represent the starting point for the development of novel patient-centered microglial approaches and in vitro modeling. 5 In a Related Article published recently in STEM CELLS, L'Episcopo et al demonstrated that the transplantation of syngeneic neural stem cells (NSCs) within the substantia nigra pars compacta in an aged mouse model of Parkinson's disease prompted the restoration of functionality thanks, in part, to the induction of Wnt/β-catenin signaling in microglia. 6 Although the bone morphogenetic protein (BMP) family of ligands were originally identified as osteoinductive components, they are now understood to impact a range of processes associated with embryonic development (including cardiogenesis, neurogenesis, and osteogenesis) and adult homeostasis by regulating cell lineage commitment, morphogenesis, differentiation, proliferation, and apoptosis of various types of cells throughout the body.…”
mentioning
confidence: 99%